Clinical impact of Endoscopic Surgical Skill Qualification System (ESSQS) by Japan Society for Endoscopic Surgery (JSES) for laparoscopic distal gastrectomy and low anterior resection based on the National Clinical Database (NCD) registry. Issue 6 (31st August 2020) - Akagi, Tomonori; Endo, Hideki; Inomata, Masafumi; Yamamoto, Hiroyuki; Mori, Toshiyuki; Kojima, Kazuyuki; Kuroyanagi, Hiroya; Sakai, Yoshiharu; Nakajima, Kentaro; Shiroshita, Hidefumi; Etoh, Tsuyoshi; Saida, Yoshihisa; et al.
Abstract: Aim: This study aimed to evaluate the association between surgeons certified via the Endoscopic Surgical Skill Qualification System (ESSQS) of the Japan Society for Endoscopic Surgery (JSES) and surgical outcomes of laparoscopic distal gastrectomy (LDG) and laparoscopic low anterior resection (LLAR). Methods: Japanese National Clinical Database data on the patients undergoing LDG and LLAR between 2014‐2016 were analyzed retrospectively. The proportion of cases performed by ESSQS‐certified surgeons was calculated for each procedure, and clinicopathological factors with or without participation of ESSQS‐certified surgeons as an operator were assessed. Then, effects of operations performed by ESSQS‐certified surgeons on short‐term patient outcomes were analyzed using generalized estimating equations logistic regression analysis. Results: There were 110 610 and 65 717 patients who underwent LDG and LLAR, respectively. The operations performed by ESSQS‐certified surgeons in each procedure totaled 28 467 (35.3%) and 12 866 (31.2%), respectively. A multivariable logistic regression model showed that odds ratios of mortality for LDG and LLAR performed by ESSQS‐certified surgeons were 0.774 (95% CI, 0.566‐1.060, P  = 0.108) and 0.977 (0.591‐1.301, P  = 0.514), respectively. Odds ratios for secondary endpoints of anastomotic leakage in LDG and LLAR performed by ESSQS‐certified surgeons were 0.835 (95% CI, 0.723‐0.964, P  = 0.014) and 0.929 (0.860‐1.003, P  = 0.059), respectively, whereas that of ileus/bowel obstruction for LLAR performed by ESSQS‐certified surgeons was 1.265 (1.132‐1.415, P  < 0.001). There were no significant associations between the two operations performed by ESSQS‐certified surgeons and other factors such as mortality and overall complications. Conclusions: ESSQS certification did not affect postoperative mortality following LDG and LLAR, but annual experience of laparoscopic surgery was associated with it. ESSQS certification may contribute to favorable outcomes regarding anastomotic leakage following LDG and LLAR. Abstract : This study aimed to evaluate the association between surgeons certified via the Endoscopic Surgical Skill Qualification System (ESSQS) of the Japan Society for Endoscopic Surgery (JSES) and surgical outcomes of laparoscopic distal gastrectomy (LDG) and laparoscopic low anterior resection (LLAR). The ESSQS contributes to favorable outcomes regarding anastomotic leakage following LDG and LLAR.